The ontogeny of morphological traits in three European species of Cosmochthonius Berlese, 1910 (Acari: Oribatida: Cosmochthoniidae) - Seniczak, Stanisław; Penttinen, Ritva; Seniczak, Anna (Zootaxa, 2011)
The morphology of juvenile stages and ontogeny of Cosmochthonius reticulatus Grandjean, 1947, C. foliatus Subías, 1982, and C. ugamaensis Gordeeva, 1980 are described and illustrated for the first time, and compared to the adults. Juveniles of these species differ mainly by the number of cilia on hypertrophied setae of e- and f-series, the shape of seta h 1 in the larva, and the shape of posterior gastronotal setae in nymphs. Cosmochthonius reticulatus has the fewest cilia on these setae, while the larva of C. ugamaensis and the nymphs and adult of C. foliatus have the most. In all species the number of cilia increases during ontogeny, more so in C. foliatus than in C. ugamaensis and C. reticulatus. Adults of these species differ mainly by the pattern of cerotegument and cuticle, best seen in SEM micrographs. Apparent in light microscopy the pygidium of C. reticulatus is reticulate, that of C. foliatus has rounded foveae, while that of C. ugamaensis has small circles and semicircles. The cuticle of the latter species is covered with thin, granular cerotegument, while that of the other species has thick, netlike cerotegument; C. foliatus also has a cerotegumental collar. Adults of all species differ also by the shape of posterior notogastral setae, and the location of some genital setae.